The effect of a mindful mothering nursing intervention virtual program on mothers with adverse childhood experiences: a randomized controlled trial - Cho, Eunjeong; Shin, Gisoo (Frontiers in Public Health, 2025)
BackgroundMothers who have experienced adverse childhood experiences often exhibit negative parenting attitudes and behaviors.ObjectivesThe study we are submitting for consideration is a randomized controlled trial that developed and implemented a mindful mothering nursing intervention virtual program for mothers who have experienced adverse childhood experiences. The primary aim of the study was to evaluate the effectiveness of this intervention.SubjectsThe participants of this study comprised 60 mothers who were raising children aged 3 to 7 and had experienced adverse childhood experiences before the age of 18. The participants were randomly assigned to either the experimental group or the control group.ToolsThe mindful mothering nursing intervention virtual program was administered to the experimental group over a period of 6 weeks, from June 20 to July 29, 2022. The intervention consisted of weekly sessions, each lasting 120 min, for a total of six sessions. The program covered a range of topics including self-understanding, awareness of adverse childhood experiences, mindfulness based parenting and emotional regulation techniques, understanding children’s physical and emotional developmental stages and corresponding parenting attitudes, emotion coaching and child acceptance, strategies for utilizing social support, professional counseling, and self-reflection. To evaluate the effectiveness of the intervention, validated instruments were used to measure adverse childhood experiences, parenting stress, parenting efficacy, mindful parenting attitude, perceived social support, and parenting behavior. Data collection was conducted both prior to the intervention and again 48 h after its completion.ResultIn this study, the experimental group showed a statistically significant reduction in mean scores for parenting stress, an increase in parenting efficacy, an improvement in mindful parenting attitude, and more positive parenting behavior compared to the control group. However, there was no statistically significant difference between the two groups in perceived social support (p < 0.05).ImplicationsThis underscores the importance of actively implementing parenting nursing interventions for mothers who have experienced adverse childhood experiences to prevent the intergenerational transmission of adverse childhood experiences.ConclusionBased on the findings of this study, the development of various parenting nursing intervention programs to support mothers with adverse childhood experiences is essential.Clinical trial registrationhttps://cris.nih.go.kr/cris/search/detailSearch.do?seq=21959&search_page=L, identifier KCT 0007353.